(untitled) (Nordic Journal of African Studies, 2004)
The paper discusses linguistic purism with reference to speakers of Chitumbuka in Malawi. Chitumbuka, along with other Malawian languages (except Chichewa/Chinyanja), was marginalised by the dictatorial regime of President Banda (1964-1994). One of the fruits of the post-Banda political dispensation has been the freedom to form language and cultural associations - and the Chitumbuka Language and Culture Association (CLACA) is one example. One of CLACA’s self-given responsibilities is that of a language guardian. In keeping with this role, CLACA has made a number of pronouncements aimed at determining, for example, what the "real" Chitumbuka is; who the "genuine" speakers of Chitumbuka are; and what culturally corrosive issues should be excluded from Chitumbuka-medium textbooks; and so on. All these concerns boil down to the fear of loss of Chitumbuka’s purity and/or the fear of Tumbuka cultural erosion. This paper points to the futility of attempts to keep language and culture pure.